Water-soluble polysaccharide obtained from Acorus calamus L. classically activates macrophages and stimulates Th1 response; International Immunopharmacology; Vol. 10, iss. 2 - Belska N.V.; Guriev A. M.; Danilets M. G.; Trophimova E. S.; Uchasova E. G.; Ligatcheva A. A.; Belousov M. V. Mikhail Valerievich; Agaphonov V. I.; Golovchenko V. G.; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Belsky Y. P. (2010, 2010)
Title screen